La agresividad familiar y su incidencia en el desarrollo formativo de las niñas y niños de 2 a 4 años que asisten al CIBV Buenos Aires, comunidad Quisquinchir, parroquia y cantón Saraguro provincia de Loja, periodo 2012 – 2013 - Zhingre Lozano, Nancy del Rocio (2014)
In the investigation process he/she intended as general objective to make aware the mothers promoters and family parents on the causes that it generates THE AGGRESSIVENESS IN THE FORMATIVE DEVELOPMENT OF THE GIRLS AND CHILDREN OF THE INFANTILE CENTER OF THE GOOD one to LIVE OFF THE COMMUNITY QUISQUINCHIR, PARISH AND CANTON SARAGURO, COUNTY DE LOJA YEAR LECTIVO 2012 -2013. The used methodology was conformed for: the scientific, synthetic, deductive method - inductive, dialectical, descriptive and the statistical method that I facilitate the field investigation stops then to open the way to the development of the tabulation of data, squares and graphic representation of the facts that I present the investigation, in a same way they were used the technique from the survey to the family parents, and to the promoters, observation record that was good to measure the grade of aggressiveness in the children and knowledge how many of them they present bigger or smaller grade of the same one. Of the 25 children and family parents and 2 mothers community selected promoters of the Infantile Center of the Good one to Live "Buenos Aires", for the present thesis, one worked with the whole population corresponding to 100%. In the process of the investigation he/she was discovered that in some cases discussions exist among the couple, what generates in the boy feelings of fear or anger, and this the exteriorizan with other partners in their behavior forms, either with aggressions or tantrums. The most frequent problems that face the families are the bad performance of the progenitors in front of the children. The emotional characteristics that the children / ace present in more percentage are the aggressiveness. Among the main results of the investigation it was found that the causes of the behavior of the children are given from the home, they act as their parents act. This behavior also impacts in a direct way in the formative development of the girls and children. Likewise it was known that the children that present aggressiveness also spread to have tantrums, which the community promoters are about fixing transforming this way into mediators, which allows them to speak with the children and to maintain a more welcoming atmosphere for the same one and to avoid as much as possible that cases are given among the children. With all that mentioned previously of the carried out investigation, you concluded that the aggressiveness if it affects in the formative development of the girls and children, and it is recommended that the family parents should maintain a harmony in the home, paying attention to their children and demonstrating the values with the example. Since the aggressiveness affects in the formative development, and children without index of aggressiveness they improved its capacities for a better coexistence for I get same and with the other ones.